Integrasi Panel Surya dengan Modul Termoelektrik sebagai Sistem Pendingin Ruangan Bertenaga Surya - Nazilul Muttaqin Nautica; Rifky (Prosiding Seminar Nasional Teknoka, 2023)
Solar energy, as a renewable energy source, can be utilized as a power generator for room cooling systems. The room cooling system receives electrical energy supply from the conversion of solar radiation through solar panels. Subsequently, this solar generator system is integrated with thermoelectric modules to produce a cold condition within the cooling system. The objective of this research is to achieve maximum heat absorption by the thermoelectric cooler in the room cooling system, determine the lowest attainable temperature, and evaluate the coefficient of performance of the cooling system. The method employed is an experimental approach, utilizing a room cooling model represented by a 0.25 m3 volume cooling box. The solar cells, serving as the power source, are oriented towards the north to maximize sunlight intensity over an extended period. The solar cell output, in the form of electrical and thermal energy, is supplied to the thermoelectric cooling system arranged in series. When electrical power is applied to the thermoelectric modules, temperature changes occur on both sides. The cold side absorbs heat from the cooling space, while the hot side releases heat into the environment. The use of a heatsink on the cold side enhances heat absorption. After conducting experiments, data collection, and processing, the overall solar cell output is determined to be 413.23 W. Meanwhile, the thermoelectric cooler achieves a minimum temperature of 24.6°C. The total heat load is found to be 416.70 W, resulting in a coefficient of performance for the cooling system of 1.01.